2006
DOI: 10.1111/j.1572-0241.2006.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Evaluation of Perianal Fistula Activity by Means of Anal Ultrasound in Patients with Crohn's Disease

Abstract: Anal ultrasound can be used to assess fistula track activity in patients with Crohn's disease. The diagnostic performance of the technique can be improved to values comparable with those of magnetic resonance imaging by using a computer-assisted evaluation of the anal ultrasound images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…In the assessment of perianal disease activity, MRI has proved to be more accurate than EUS [28]. However, the accuracy of EUS can be increased by computerized evaluation of US images as demonstrated by Caprioli et al who reported an increased diagnostic accuracy of EUS by using computerized image analysis, thereby achieving results which were similar to those of pelvic MRI.…”
Section: Diagnosis: the Role Of Imaging Techniquesmentioning
confidence: 62%
See 1 more Smart Citation
“…In the assessment of perianal disease activity, MRI has proved to be more accurate than EUS [28]. However, the accuracy of EUS can be increased by computerized evaluation of US images as demonstrated by Caprioli et al who reported an increased diagnostic accuracy of EUS by using computerized image analysis, thereby achieving results which were similar to those of pelvic MRI.…”
Section: Diagnosis: the Role Of Imaging Techniquesmentioning
confidence: 62%
“…Similarly, at EUS, a fistula is considered active if it appears strongly hypoechoic, possibly with hyperechoic internal echoes as a result of a predominantly liquid content and the presence of gas bubbles deriving from suppurative inflammation [25][26][27][28] (Figs. 3, 4, 5).…”
Section: Diagnosis: the Role Of Imaging Techniquesmentioning
confidence: 99%
“…Ultrasonographic findings showing that satisfaction of two or all three criteria are satisfied may simply represent the sequel of more severe disease of longer duration that had been subjected to repeated unsuccessful surgery. It has been proposed that the hyperechoic content of the fistula tract is a sign of inflammatory activity of the fistula tract or of perianal disease as a whole [5,6]. The same type of secretions inside the fistula can also be observed by means of magnetic resonance imaging [7].…”
Section: Discussionmentioning
confidence: 98%
“…23,24 It is possible that a computer-based assessment of the degree of hypoechogenicity of the intersphincteric abscess might help improve the imaging-based definition of inactive lesions, as previously reported for fistulating disease. 12,25 In conclusion, intersphincteric abscesses frequently cause perianal pain in patients with CD attending a tertiary gastroenterological referral center, and should be suspected in the presence of unexplained anal pain, particularly if a fissure is palpable in the anal canal. The clinical outcome of these abscesses varies from rapidly progressive inflammation to a benign self-limiting course, but the favorable outcome observed in some patients supports a first-line conservative approach.…”
Section: Discussionmentioning
confidence: 98%
“…as previously described 12 using a Brüel and Kjaer ultrasound scanner (Falcon 2101 EXL, Herlev, Denmark) equipped with a 10 MHz rotating transducer (type 1850, transducer tip 6004) that provides a 360 cross-sectional image of the anal sphincters. Another operator (A.L., C.V., or F.C.)…”
Section: Ausmentioning
confidence: 99%